Efficacy of lidocaine-prilocaine combination cream in reducing pain caused by hepatitis B injection in neonates: a randomized control trial - Nugroho Karyadiguna; Soetjiningsih Soetjiningsih; W. Retayasa; M. Kardana (Indonesian Pediatric Society, 2007)
Background Many invasive medical procedures cause pain inneonates. Pain in this age group increases morbidity, impairsemotional bonding, and causes hyperalgesia. Combination oflidocaine and prilocaine cream is one of the topical analgesicsthat are easy to use and safe for neonates.Objective To assess the efficacy of lidocaine-prilocainecombination cream in reducing pain caused by intramuscularinjection of hepatitis B and to find out the correlation of sex,gestational age, birth weight, chronological age, and method ofdelivery with infant’s pain response.Methods A double blind randomized controlled trial wasconducted on term neonates. Subjects were selected consecutivelyand every subject was randomized to either receive lidocaine-prilocaine cream or placebo one hour prior to administration ofintramuscular hepatitis B vaccine. The administration wasrecorded by a handycam and the intensity of pain responses wasevaluated using DAN (Douleur Aigue Nouveau-ne) scale.Results Of 67 subjects, the mean of DAN scale was 7.60 (95%CI 7.27;7.95) in the lidocaine-prilocaine cream group and thiswas significantly lower (P<0.0001) than in placebo group, whichwas 8.82 (95% CI 8.56;9.09). ANCOVA showed that there wereno associations between sex, gestational age, birth weight,chronological age, and method of delivery with infant’s painresponse.Conclusion Lidocaine-prilocaine combination cream can reducethe pain caused by intramuscular injection of hepatitis B vaccineon term neonates.